2020
DOI: 10.3390/ma13112430
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Properties of the Copper Alloyed with Ag and Ti Powders Using Fiber Laser

Abstract: The scope of the work covers the development of the relationship between the chemical composition of surface-modified copper and the diffusion of alloy elements as well as the microstructure and mechanical properties. This article presents the impact of laser alloying with titanium and silver powders on the microstructure and mechanical properties of copper. In order to investigate the phenomena occurring during the laser alloying process, microstructural studies were performed using scanning electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…As a result of laser heat treatment within the remelting zone, grain growth was observed (Figure 5 -6). The RZ after alloying process showed directional solidification, which towards to the front of the heat dissipation [19]. After observing the microstructure changes after alloying, a hardness measurement was performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of laser heat treatment within the remelting zone, grain growth was observed (Figure 5 -6). The RZ after alloying process showed directional solidification, which towards to the front of the heat dissipation [19]. After observing the microstructure changes after alloying, a hardness measurement was performed.…”
Section: Resultsmentioning
confidence: 99%
“…The volume of wear was decreased of 98% after laser alloying. Presumably, it happened due to precipitation of intermetallic phases [19].…”
Section: Discussionmentioning
confidence: 99%
“…In our case, regarding the 3-Polker coins, this concerns the Ag–Cu binary system, which is a system with total insolubility and that has an eutectic at the composition of 719 ‰ Ag and 281 ‰ Cu weight percent [ 17 , 18 ]. Metallographic microscopy is one of the most powerful tools used to investigate alloys’ microstructures [ 17 , 19 , 20 ], but it requires local grinding and polishing prior to chemical etching and it is not effective for application to small coins that have been heavily exposed. Some powerful non-destructive methods are required in our case.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the wear resistance of laser-alloyed specimens was improved. The influence of laser alloying of titanium and silver powders on the microstructure and mechanical properties of copper was also investigated [ 10 ]. It was found that laser surface alloying with Ti powder increased the strength in the copper surface layer due to the formation of intermetallic phases (Cu 3 Ti 2 ), while laser alloying with Ag powder changed the mechanical properties of the surface layer by solid solution strengthening.…”
Section: Introductionmentioning
confidence: 99%